Ponatinib Protects Mice From Lethal Influenza Infection by Suppressing Cytokine Storm - Chen, Si; Liu, Ge; Chen, Jungang; Hu, Ao; Zhang, Li; Sun, Wenyu; Tang, Wei; Liu, Chunlan; Zhang, Haiwei; Ke, Chang; Wu, Jianguo; Chen, Xulin (Frontiers in Immunology, 2019)
Excessive inflammation associated with the uncontrolled release of proinflammatory cytokines is the main cause of death from influenza virus infection. Previous studies have indicated that inhibition of interferon gamma-induced protein 10 (IP-10), interleukin-8 (IL-8), monocyte chemoattractant protein 1 (MCP-1), or their cognate receptors has beneficial effects. Here, by using monocytic U937 cells that capable of secreting the three important cytokines during influenza A virus infection, we measured the inhibitory activities on the production of three cytokines of six anti-inflammatory compounds reported in other models of inflammation. We found that ponatinib had a highly inhibitory effect on the production of all three cytokines. We tested ponatinib in a mouse influenza model to assess its therapeutic effects with different doses and administration times and found that the delayed administration of ponatinib was protective against lethal influenza A virus infection without reducing virus titers. Therefore, we suggest that ponatinib may serve as a new immunomodulator in the treatment of influenza.